#TITLE_ALTERNATIVE# - REZA ISLAMI SUKMAJATI (NIM : 12213025), R.
Tracer testing is used in the petroleum industry in order to measure qualitatively or quantitatively how the fluid passes through the reservoir. Tracer testing is divided into two kinds, Interwell Chemical Tracer Test (IWTT) and Single Well Chemical Tracer Test (SWTT). In the Interwell Tracer Test, the tracer is injected to an injector well along with the carrier fluid (in this case water on the waterflood) and will be detected at the monitor well after a while, which may be from day to year. Detected tracer result data on field T can be used to illustrate how the fluid flow in the reservoir from the injector well to the monitor well on field T. From this tracer result data we will get the tracer concentration detected when sampling is done within a certain period of time, data time breakthrough tracer at the monitor well, and cumulative fluid that is produced at monitor well. With additional data available such as density and mass tracer injected, the interpretation of tracer results data can be done using the Moment Analysis Method developed by Michael Shook, with the results obtained in the form of parameters such as sweep efficiency by injection fluid from the injector well to the monitor well , The number of tracer masses detected at the monitor well, as well as the heterogeneity of the reservoir either in the area (expressed by Lorentz Coefficient) also vertically (expressed by Dykstra-Parson Coefficient) along the area from the injector well to the monitor well. The reservoir properties to be determined in this study are the permeability levels of the heterogeneous reservoir. Due to its heterogeneous nature, this reservoir has different permeability values in each layer and is expressed qualitatively. With the integration of studies using well logging data and vertical heterogeneity values interpreted by Interwell Tracer Test, the qualitative permeability values can be determined. This study concludes that the Interwell Tracer Test is a good method to find out how the flow pattern in the reservoir from the injector well to the monitor well. In general, the results of the tracer data interpretation show that the flow pattern of the injector wells will be more dominant to the monitor well with a relatively more homogeneous area around the well with assumption that lateral permeability in reservoir is homogeny. Furthermore, the vertical heterogeneity of tracer data interpretation can be used or translated to a reservoir properties value that is qualitatively permeable with the support of well logging data from the wells reviewed. And the value of these permissions can also support flow patterns according to the conclusions that have been delivered at the beginning.